PENGARUH MOTIVASI INSTRINSIK, MOTIVASI EKSTRINSIK DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI KANTOR POS PALANGKARAYA - Tania Desfira Putri Rosyana; Rita Yuanita Toendan; Peridawaty (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
The Influence of Instrinsic Motivation, Extrinsic Motivation and Work Environment on Employee Performance of Palangka Raya Post Office. This study aims to determine the effect of Instrinsic Motivation, Extrinsic Motivation and the Work Environment on Employee Performance of the Palangka Raya Post Office. The research method used an explanatory approach with survey techniques, the number of samples in this study were 45 respondents, the sampling technique used the Census technique. Data collection methods used interview techniques, observation, questionnaires, and documentation studies, while the data analysis techniques used in this study were using descriptive analysis techniques and multiple linear analysis techniques.The results showed that Instrinsic Motivation, Extrinsic Motivation and Work Environment had a significant effect on Employee Performance Performance at Palangka Raya Post Office. And the results of the descriptive analysis state that the respondents agree with the indicators proposed